Exploring the quadratic nature of the relationship between strength & performance in shot putters - Judge, L. W.; Bellar, D. (World Congress of Performance Analysis of Sport IX, 2012)
Power is the mechanical quantity that expresses the rate of performing work and is largely dependent upon peak force production (i.e., maximum strength) (Stone et al., 2003). Although the value of strength to shot putting appears undisputable, several authors have recommended that explosive power is actually a more important physical characteristic (Bartonietz et al., 1997). The purpose of this study was to investigate the relationship of the 1RM in the power clean to shot put event performance. A survey instrument was developed to collect data regarding national level collegiate shot putters in the United States. The 24 males (22.2 +/- 2.2 years) and 29 females (22.5 +/- 2.8 years) athletes had a mean personal best performance of 16.93 +/- 2.45 meters for the men and the women 15.24 +/- 2.85 meters. The sample included several national qualifiers, two national champions in shot put and three Olympians. Trends in the relationship between 1RM power clean and personal best in the shot put for male and female athletes were assessed via general linear model polynomial contrast analysis, and subsequent polynomial regression. General linear model analysis revealed both significant omnibus tests of the models (male likelihood ratio Chi2 = 56.716, p.0.001, female likelihood ratio Chi2 = 102.516, p.0.001) and significant linear and quadratic trends in the data for male and female shot put athletes when comparing 1RM power clean to personal best distance (male: Wald Chi2 = 179.937, p.0.001 linear, Wald Chi2 = 8.598, p=0.003 quadratic; female: Chi2 ƒÔ2 = 738.577, p.0.001 linear, Wald Chi2 = 134.864, p.0.001 quadratic). Quadratic regression analysis resulted in strong curve fitting with both male (r=0.873, F=33.496, p.0.001) and female (r=0.904, F=55.867, p.0.001) athletes data. The understanding that there are both linear and curvilinear trends in the association between strength and performance potentially can enrich the understanding of this association. The quadratic regression analysis revealed that athletes towards the outer ranges of performance in the shot put require greater levels of increasing strength in order to obtain the associated distances.